THE PROBLEM OF FOOD SHORTAGE AND MEASURES TO SOLVE IT - D.A.Xudoyqulova (International Scientific and Current Research Conferences, 2023)
Nowadays, many people are suffering due to the problem of food shortage, which is becoming a topical issue. Mainly, improper irrigation of lands destroys soil structure. This leads to a decrease in the productivity of agricultural products. Excessive use of pesticides and herbicides to protect products from various pests has a negative impact on human health. In order to avoid such negative consequences, it is advisable to establish proper irrigation and to grow natural, clean products as much as possible.